2022
DOI: 10.1186/s12991-022-00380-8
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism and suicide risk

Abstract: We all have narcissism, but in some cases, the perception of narcissism becomes extreme and pathological. Systematic research has shown that there are three subtypes typical of narcissistic personality disorder: the grandiose/oblivious, the vulnerable/hypervigilant, and the high-functioning subtype. Both biological and psychological factors are at work, but the true cause of pathological narcissism has not been established. The psychotherapy of narcissistic personality disorder (NPD) is complicated and often f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…However, it was recognized that traits such as charm and selfconfidence, fearlessness and low reactivity to stress could probably be favorable in the workplace [32]. Conversely, few studies are available specifically investigating the personal consequences that may affect individuals with high DT scores, being most of these which focus on the increased risk of depressive episodes or suicidal behaviors [18,99].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was recognized that traits such as charm and selfconfidence, fearlessness and low reactivity to stress could probably be favorable in the workplace [32]. Conversely, few studies are available specifically investigating the personal consequences that may affect individuals with high DT scores, being most of these which focus on the increased risk of depressive episodes or suicidal behaviors [18,99].…”
Section: Discussionmentioning
confidence: 99%
“…Coherently, several research studies demonstrated no apparent relationship between narcissism and depression [16,18]. However, suicidal ideation and risk is not rare in individuals with narcissism traits, even though the wish to kill oneself can also emerge without the presence of a clinically relevant depressed state [98,99]. Within this context, suicidal ideation and feelings usually may grow out as a consequence of the desperate need to regulate own's self-esteem and protect a pathological selfimage of perfection [99].…”
Section: Regardingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, clinicians often associate these symptoms with the BPD diagnosis, and patients with ED often fulfill criteria for BPD, even if it is now well-known that ED can also be encountered in many other psychiatric disorders than BPD, and is currently considered as a transdiagnostic construct (8)(9)(10). In the field of personality pathology, patients suffering from pathological narcissism (PN) (with/without narcissistic personality disorder, NPD), obsessive-compulsive personality disorder (OCPD) and antisocial personality disorder (ASPD) may also present several of the above mentioned symptoms of ED (11)(12)(13)(14)(15)(16)(17)(18). Apart from the field of personality disorders, ED can also be found in patients suffering from bipolar disorder [BD, (19,20)], autism spectrum disorder [ASD, (21,22)], complex post-traumatic stress disorder [cPTSD, (23)] and adult attention deficit hyperactivity disorder [ADHD, (24,25)].…”
Section: Introductionmentioning
confidence: 99%